2015
DOI: 10.3892/br.2015.561
|View full text |Cite
|
Sign up to set email alerts
|

Pim-1 kinase as cancer drug target: An update

Abstract: Proviral integration site for Moloney murine leukemia virus-1 (Pim-1) is a serine/threonine kinase that regulates multiple cellular functions such as cell cycle, cell survival, drug resistance. Aberrant elevation of Pim-1 kinase is associated with numerous types of cancer. Two distinct isoforms of Pim-1 (Pim-1S and Pim-1L) show distinct cellular functions. Pim-1S predominately localizes to the nucleus and Pim-1L localizes to plasma membrane for drug resistance. Recent studies show that mitochondrial Pim-1 main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 69 publications
1
74
0
Order By: Relevance
“…Pim1 kinase is part of the serinethreonine protein kinases that play a role in apoptosis, metabolism, cycles, and migration of cells in tumor growth. Pim1 kinase is also overexpressed in several types of human cancers and it's activity also reported as a promoter of carcinogenesis, so that it is postulated as a potential target of cancer therapy (Tursynbay et al, 2016;Matthew et al, 2015;Weirauch et al, 2013). Pim1 downloaded from PDB with ID code of 5 wdr selected due to has a resolution of 2Å, descended from Homo sapiens and complexes with a small molecule ligand of [N-4-(1R,3S,5S)-3-amino-5-methylcyclohexylpyridine-3-yl-6-(2,6-difluorophenyl)-5fluoropicolinamide (5H7_401(A)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pim1 kinase is part of the serinethreonine protein kinases that play a role in apoptosis, metabolism, cycles, and migration of cells in tumor growth. Pim1 kinase is also overexpressed in several types of human cancers and it's activity also reported as a promoter of carcinogenesis, so that it is postulated as a potential target of cancer therapy (Tursynbay et al, 2016;Matthew et al, 2015;Weirauch et al, 2013). Pim1 downloaded from PDB with ID code of 5 wdr selected due to has a resolution of 2Å, descended from Homo sapiens and complexes with a small molecule ligand of [N-4-(1R,3S,5S)-3-amino-5-methylcyclohexylpyridine-3-yl-6-(2,6-difluorophenyl)-5fluoropicolinamide (5H7_401(A)].…”
Section: Resultsmentioning
confidence: 99%
“…Pim1 kinase is overexpressed in many human cancer diseases and has been associated with metastasis and overall treatment response. The experimental model study reported that inhibition of Pim1 kinase suppressed proliferation and migration cell, induced apoptotic cell death, and synergized with other chemotherapeutic agents so that Pim1 kinase is the preferential target for inhibition of the mitotic processing and can be chosen as drug target for the treatment of cancer (Gisele et al, 2016;Tursynbay et al, 2016;Matthew et al, 2015;Weirauch et al, 2013). Some compounds were reported to inhibit the activity of serine/threonine kinases of Pim1, such as imidazopyridazine, benzoimidazol, acylhydrazone, triazolopyridine, thiazolidine-2,4-dione, pyridone, staurosporin, and bisindolylmaleimide (Merkel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of PIM 1 expression has been shown in prostate cancer following inhibition of AKT [20], providing further evidence for the idea of crosstalk between both PIM kinase and PI3K/AKT/mTOR pathways [21]. Inhibition of AKT can also induce increased expression of several different receptor tyrosine kinases such as HER2 through PIM 1-mediated regulation [2,22].…”
Section: Introductionmentioning
confidence: 82%
“…In this study, we have determined that elevated expression of PIM 1 is significantly associated with elevated sensitivity to IBL-302 in both TNBC and HER2+/ER+ cell lines. PIM 1 has been highlighted as a therapeutic target in TNBC [12,14,60] and as a result, not much focus has been placed on HER2+/ER+ cells, especially those with acquired resistance to HER2 targeted therapies. Interestingly, there is high PIM 1 expression in the HER2+ HCC-1954 cells, whilst the PIK3CA mutant BT-474 cells, which have low expression of PIM 1, are also sensitive to IBL-302.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation